Mrs. Mac Swiney arrives from Ireland - International Newsreel Corporation, photographers (1920)
Title on note attached to verso of three copies continues "Mrs. Muriel MacSwiney, widow of the Lord Mayor of Cork, arriving in New York from Ireland today on the S.S.Celtic. She was given a wonderful reception by sympathizers of the irish cause. Mrs. MacSwiney, after a short stay in New York will go to Washington to testify before the American Committee on Ireland. Includes note "Watch Your Credit Line 123406-International".